2012
DOI: 10.1007/s11657-012-0104-1
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of vitamin D inadequacy and dress style of women in the sunny UAE

Abstract: The pattern and longevity of dressing style should not be used as pretext for the hypovitaminosis D before other factors are being examined or considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
3
19
1
Order By: Relevance
“…Similar to the findings in the UAE reported by Al Attia et al [33], no difference was noted by Fawzi et al in the prevalence of vitamin D insufficiency (25(OH)D < 50 nmol/L) or inadequacy (25(OH)D 50–72.5 nmol/L) in Western (30.6% insufficient; 44.4% inadequate), Hegab (34.9% insufficient; 46.5% inadequate) or Nekab (29.4% insufficient; 52.9% inadequate) dress styles [36]. Botros et al studied 208 women with a mean age of 31.5 years, and reported vitamin D insufficiency in 72% (serum 25(OH)D < 50 nmol/L) [27].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the findings in the UAE reported by Al Attia et al [33], no difference was noted by Fawzi et al in the prevalence of vitamin D insufficiency (25(OH)D < 50 nmol/L) or inadequacy (25(OH)D 50–72.5 nmol/L) in Western (30.6% insufficient; 44.4% inadequate), Hegab (34.9% insufficient; 46.5% inadequate) or Nekab (29.4% insufficient; 52.9% inadequate) dress styles [36]. Botros et al studied 208 women with a mean age of 31.5 years, and reported vitamin D insufficiency in 72% (serum 25(OH)D < 50 nmol/L) [27].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastsupporting
confidence: 92%
“…Al Attia et al reported serum 25(OH)D < 75 nmol/L in 90.5% of 255 adult women (mean age 44 years) from the UAE [33]. Interestingly, traditional clothing was not found to significantly affect vitamin D status, with observed rates of serum 25(OH)D < 75 nmol/L equally high among women who were fully veiled, veiled with hands and face exposed, and those who were unveiled (i.e., wearing Western clothing).…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Checking for vitamin D level is very commonly requested by both patients and doctors in our hospital. Furthermore, it is difficult to distinguish between healthy people and patients in regard to this condition; as mentioned above, previous studies have reported frequencies of up to 90% vitamin D deficiency/insufficiency in "healthy" subjects (12,13).…”
Section: Limitationsmentioning
confidence: 99%
“…Vitamin D insufficiency (30−50 ng/ mL) has been reported in up to 80% of Saudi Arabian girls and women (10) and Kuwaiti women (11), and in up to 90% of the population of Qatar (12) and the female population in the United Arab Emirates (13). The United Arab Emirates has an average of 10 hours of sunshine per day, which should favour vitamin D synthesis all year round (2,14).…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of sunlight exposure and the influence on vitamin D level are determined much more by the dressing and clothing style [68,69]. Significant hypovitaminosis D but not OP was observed in women categorized into groups according to the longevity of dressing [70]. In Moroccan and Turkish women, wearing traditional clothing covering arms, legs and head, the risk of OP was increased [10,71].…”
Section: Menopause and Paritymentioning
confidence: 99%